Ceramic Hollow Fiber Membranes As New Filter Media And Their Application In Oil/Water Separation Processes - Schütz, Steffen; Ehlen, Frank; Unger, Ina; Kariveti, Sreenath; Wang, Can; Ebrahimi, Mehrdad; Kerker, Steffen; Czermak, Peter (My University, 2015)
Ceramic membranes become continuously attractive for separation applications with fluids at increased temperatures, at high or low pH levels and in contact with critical chemical species as solvents or other organic components when polymeric membranes often fail due to high fouling or material instability. A ceramic hollow fiber membrane was developed at MANN+HUMMEL, see Figure 1. This ceramic hollow fiber membrane shows the advantages of a high volumetric filtration area and low material volumes compared to ceramic membranes with other geometries. The specific design of this membrane comprises a microfiltration ceramic support layer and an ultrafiltration ceramic functional separation layer with a pore size d90 = 40 nm. This two layer structure leads to high membrane fluxes and low pressure drop during operation. The membrane operation in cross flow mode allows the control of fouling layers due to the applied cross flow velocity. Figure 1: Cross-section of a ceramic hollow fiber membrane (MANN+HUMMEL). The operation behavior of this ceramic hollow fiber membrane was investigated for oil/water separation applications in close cooperation with a research partner and in application tests with customers. It was shown that the membrane can be operated with high oil loads up to 5000 ppm in the waste water without requiring a pretreatment. The oil contents in the permeate water were reduced to 1 ppm. Pure mechanical backflushing with permeate water was sufficient to clean the membrane in place and to reach nearly the initial flux values of the new membrane during operation. The robustness of the membrane operation in industrial applications was shown by running the membranes for several weeks in water treatment processes with industrial waste water. The waste water treatment was also promising when additional high solid loads contaminated oily waste water to be cleaned.
Citation: Steffen Schütz, Frank Ehlen, Ina Unger, Sreenath Kariveti, Can Wang, Mehrdad Ebrahimi, Steffen Kerker, Peter Czermak: CERAMIC HOLLOW FIBER MEMBRANES AS NEW FILTER MEDIA AND THEIR APPLICATION IN OIL/WATER SEPARATION PROCESSES, in Proceedings FILTECH 2015, 24-25. February 2015, Cologne
Keywords: Ceramic Membrane; Hollow Fiber Membrane; Oil Content; Produced Water